The Relation of Obesity and Individual Factors with Knee Osteoarthritis - Niken Enestasia Anggraini; Lucia Yovita Hendrati (Universitas Airlangga, 2014)
Osteoarthritis represent disease at most found in the world, including in Indonesia. This disease cause pain in bone and disability at patient so disturb everyday activity. One of removed occurrence of knee Osteoarthritis was obesity. Other factors like age, gender, physical activity, and habit smoke were risk factors of knee Osteoarthritis . This research was the relationship of obesitas and individuals factors with occurrence knee osteoarthritis at Surabaya Islamic Hospital. The methods of this research was an observation with case control design. Level of sampel was 64 which consist of 32 case group and 32 control group from incomed patient to radiology unit Islamic Hospital Surabaya for X-Ray photo. The dependent variable was occurence of knee osteoarthritis . The independent variables were obesity, gender, age, physical activity, habit smoke. The instrument used was a questionnaire and form Body Mass Index (BMI/IMT) measurement. Data analysis used Chi-Square test with α=0,05 and to know Odds Ratio (OR) used statclac. The results showed significant relationship between occurence of knee osteoarthritis with obesity (p = 0,001, OR = 7,20), age (p = 0,012; OR=3,67), gender (p=0,005,OR=4,69). For the characteristic of habit smoke (p=0,268,OR=0,56), and physical activity (p=0.919,OR=0,71) weren’t associated with the occurence of knee steoarthritis at Surabaya Islamic Hospital. The conclusion there is relationship between obesity and another risk factor knee osteoarthritis like gender and age with knee osteoarthritis at Surabaya Islamic Hospital.